Discovering Teachers' Perception of Adaptive Environments in Contemporary Education - Thaariq, Zahid Zufar At; Kuswandi, Dedi; Degeng, Made Duananda Kartika (Universitas Sultan Ageng Tirtayasa, 2024)
Contemporary education is characterized by its adaptability to the changing needs of society, its promotion of diversity and sustainability, and its utilization of both traditional and digital teaching methods to equip students with the necessary skills to face the challenges of the 21st century. Adaptive learning is a crucial implementation that teachers must comprehend to facilitate student-centered learning. This study aimed to investigate the perceptions of 17 randomly selected teachers from Wahid Hasyim Middle School regarding their experience of adaptive environmental management in their teaching, using factor analysis techniques. The results indicate that video and audio media are predominantly used in educational interactions, reflecting the adaptation to digital technology trends in teaching. Furthermore, course delivery, lesson planning, teaching strategies, teaching methods, learning media, and educational resources emerged as highly significant factors. The discovery and organization of content revealed a preference for student-centered approaches and student-oriented teaching strategies. Finally, supporting teacher collaboration highlights the importance of team collaboration, community engagement, and professional networks in contemporary educational development. However, this study has limitations in terms of its specific context, variable focus, and lack of causality analysis. Therefore, future research may aim to diversify the data, delve deeper into causal factors, and update the data regularly to maintain relevance in an ever-changing educational context. Thus, these findings provide valuable insights into dealing with contemporary educational dynamics.